Platelet-Rich Plasma for Burn Wound Healing in Preclinical Models: A Systematic Review of Efficacy and Biomolecular Mechanisms - George Dyland De Ussy Whandyra; Udadi Sadhana; Yuriz Bakhtiar (HM Publisher, 2025)
Background: Burn injuries represent a major global health issue, with complex pathophysiology that often leads to significant morbidity. Platelet-rich plasma (PRP) has been identified as a potential therapeutic agent due to its high concentration of growth factors that promote tissue renewal. This review synthesizes preclinical evidence on the efficacy of PRP for burn wounds. Methods: This systematic review followed PRISMA guidelines, searching PubMed, Scopus, and ScienceDirect for animal studies on PRP for burn wounds. The primary outcomes were wound healing, fibroblast scores, and VEGF/EGF levels. The SYRCLE tool was used for risk of bias assessment. Results: Eleven studies involving 526 animals were included. The risk of bias across studies was generally high or unclear, primarily due to poor reporting of randomization and blinding. Macroscopically, PRP was reported to accelerate wound closure in partial-thickness burns within 4-7 days and in full-thickness burns from day 8 onward. On a biomolecular level, PRP was associated with increased fibroblast scores and elevated tissue concentrations of VEGF and EGF from the first day post-treatment (P<0.05 in multiple studies). Conclusion: While the included studies suggest PRP may enhance healing, definitive conclusions are precluded by the high risk of bias and methodological heterogeneity across the preclinical evidence base.